2016
DOI: 10.1002/psc.2878
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CRISP2 from human sperm as PSP94‐binding protein and generation of CRISP2‐specific anti‐peptide antibodies

Abstract: Cysteine-rich secretory proteins (CRISPs) are mainly found in the mammalian male reproductive tract and reported to be involved at different stages of fertilization. CRISPs have been shown to interact with prostate secretory protein of 94 amino acids (PSP94) from diverse sources, and the binding of these evolutionarily conserved proteins across species is proposed to be of functional significance. Of the three mammalian CRISPs, PSP94-CRISP3 interaction is well characterized, and specific binding sites have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Interestingly, human CRISP-3 and CRISP-2 share 71.4. percent sequence identity. In this direction, using affinity pull down, we identified CRISP-2 as one of the probable binding proteins from human sperm to bind to PSP94 (135). Further, we pursued the development of indigenous anti-peptide antibodies against the least conserved ICR region of the CRISP domain in an attempt to distinguish human CRISP-2 from CRISP-3.…”
Section: Cysteine Rich Secretory Protein (Crisp)mentioning
confidence: 99%
“…Interestingly, human CRISP-3 and CRISP-2 share 71.4. percent sequence identity. In this direction, using affinity pull down, we identified CRISP-2 as one of the probable binding proteins from human sperm to bind to PSP94 (135). Further, we pursued the development of indigenous anti-peptide antibodies against the least conserved ICR region of the CRISP domain in an attempt to distinguish human CRISP-2 from CRISP-3.…”
Section: Cysteine Rich Secretory Protein (Crisp)mentioning
confidence: 99%
“…In contrast to CRISP3, PSP94 expression is downregulated in prostate cancer, suggesting a protective role in prostate carcinogenesis (21)(22)(23). PSP94 also interacts with another CRISP family member, CRISP2, also referred to as Tpx-1 (testis-specific protein 1), a non-glycosylated CRISP family member produced during spermatogenesis, which shares 71% sequence identity with CRISP3 (24,25). CRISP2 regulates calcium influx through ryanodine receptors to modulate sperm flagellar motility (11,26,27).…”
Section: Introductionmentioning
confidence: 99%
“…Sperm MSMB is probably involved in the interactions between spermatozoa and zona pellucida at fertilization as well as in the regulation of sperm hyperactivation at the time of sperm capacitation [11]. In a more recent study, sperm MSMB has been found to associate with CRISPs (cysteine-rich secretory proteins) [17] implicated in gamete binding and fusion [18].…”
Section: Introductionmentioning
confidence: 99%